The world's greatest aircraft carriers an illustrated history - Ross, David (Amber Books, 2017)
"The World's Greatest Aircraft Carriers features 52 of the most significant flat tops and amphibious assault ships built since the 1920s until the present day, from the USS Yorktown, which survived direct hits during the battle of Midway (1942), through the Falklands War veteran HMS Invincible, to the mighty Nimitz class, the core of the US Navy's carrier battle groups today. Also included are significant amphibious assault ships, such as the USS Tarawa and French Mistral. Each entry includes a brief description of the ship's development and history, a color profile view or cutaway, key features and specifications"